Determinants of dynamic profitability of banks: an empirical study from Chinese commercial banks - XU, WENJUN (2018)
China is the second largest economy in the world. The vibrant development of banking industry plays an important role in the whole economic lifeline of China. This paper study the various determinants of the profitability of Chinese banks during the period from 2011 to 2017. The two step System Generalized Methods of Moment (SGMM) is applied for processing a balanced bank-level panel data constituting of data from 104 commercial banks. The empirical results show that Chinese banking sector is under the comprehensive influence of internal and external factors. The internal variables include bank size, credit risk, liquidity, capital adequacy and non-traditional activity while external variables are GDP growth rate, stock market activity and concentration ratio. And we select three profitability indicators ROAA, ROAE and NIM as the dependent variables in the regression models. In addition, due to the Socialism with Chinese characteristics, China implements Socialist Market Economy System and have experienced three stages of banking reforms, accepting the guidance of the central government. As a result, the empirical results are mixed in three models and these explanatory variables have different effects on the profitability of Chinese banks.